Skill Development and Motivational Enhancement to Change Drinking Behavior in Sabah Borneo (Global Journal of Human-Social Science, 2020)
Alcohol is the third highest risk factor for disease prevalence in the world and threatens the quality of life of people and societies. Consumption of alcohol is a challenge in a few of the native communities of Sabah and Sarawak with the highest prevalence of risky drinking in Malaysia. This study aimed to compare drinking refusal self-efficacy (DRSE) and quality of life (QOL) between the experimental group and the control group before and after the Motivational Enhancement Intervention (MEI); and to compare DRSE and QOL of the experimental group before and after the MEI. A quasi-experimental design was used to assess the effectiveness of MEI at baseline and three months follow-up by using pretest and posttest design. A total of 56 villagers in the West Coast Division of Sabah participated in this study. Purposive sampling by using Alcohol Use Identification Test (AUDIT) was applied to select hazardous and harmful drinkers between age 18 to 56 years old.
Keywords: drinking refusal self-efficacy; alcohol consumption; quality of life; motivational enhancement; indigenous communities